Correlation of incontinence impact questionnaire score in overactive bladder syndrome cases with urodynamic findings - Sharma, Jai B.; Chauhan, Mukul; Bhatla, Neerja; Seth, Amlesh; Kumari, Rajesh; Uppal, Bharti; Singh, Janmeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Overactive bladder syndrome (OAB) is a common condition. The aim of the present study was to correlate the incontinence impact questionnaire (IIQ) score with urodynamic studies in patients of overactive bladder syndrome. Methods: It was a prospective study performed in a tertiary referral centre on 60 women with symptomatology of OAB. IIQ score was calculated and urodynamic studies were performed in all patients in which detrusor overactivity, maximum flow rate of urine per second (Qmax) and voiding time in seconds was calculated in all women. Results: The mean age was 42.3±9.91 years, mean body mass index was 24.7±2.71 kg/m2, mean parity was 2.4 and mean serum creatinine level was 0.84±0.21 mg/dl. Symptoms seen were urgency (100%), frequency (100%), urge incontinence (95.0%) and nocturia (76.6%). IIQ score ranged from 7-20 with mean being 12.27±3.38. OAB was mild in 36.6%, moderate in 41.66% and severe in 21.66% patients. On urodynamic studies, detrusor overactivity was present in 75% cases being 59% in mild, 80% in moderate and 76.92% in severe OAB. Mean Qmax increased with severity of OAB and was 29.55ml/second in mild OAB, 30.36ml/second in moderate OAB and 31.59 ml/second in severe OAB. Mean voiding time decreased with severity of OAB and was 33.44 seconds in mild OAB, 32.14 seconds in moderate OAB and 31.47 seconds in severe OAB. Conclusions: IIQ score and urodynamic studies are useful in diagnosis and quantification of OAB syndrome.